2020
DOI: 10.1038/s41598-020-59919-y
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of ocular biometric measurements in young healthy eyes between IOLMaster 700 and OA-2000

Abstract: This prospective cross-sectional study aimed to evaluate the agreement of two new biometers for measuring ocular biometric parameters in young healthy eyes. ocular biometric parameters were measured using IOLMaster 700 and OA-2000. Power vector analyses of Cartesian (J0) and oblique (J45) components of corneal astigmatism were performed. The right eyes of 103 healthy volunteers were analyzed. The 95% limits of agreement ranged from −0.03 to 0.03 mm, −0.08 to 0.07 mm, −0.18 to 0.18 diopters (D), −1.09 to 1.16 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 31 publications
4
45
0
1
Order By: Relevance
“…The discrepancy of the three devices in total keratometry could be caused by the different algorism for calculating total keratometry in each device [5,8,19]. IOLMaster 700 obtains anterior keratometry with 18 reflected spots in hexagonal patterns at three zones (1.5 mm, 2.5 mm, and 3.5 mm) and posterior keratometry with SS-OCT tomography [16,20]. Meanwhile, ANTERION and CASIA2 calculate anterior and total keratometry only with SS-OCT images (ANTE RION: 65 B-scans with 256 A-scans each; CASIA2: 16 B-scans with 800 A-scans each) [8,21].…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy of the three devices in total keratometry could be caused by the different algorism for calculating total keratometry in each device [5,8,19]. IOLMaster 700 obtains anterior keratometry with 18 reflected spots in hexagonal patterns at three zones (1.5 mm, 2.5 mm, and 3.5 mm) and posterior keratometry with SS-OCT tomography [16,20]. Meanwhile, ANTERION and CASIA2 calculate anterior and total keratometry only with SS-OCT images (ANTE RION: 65 B-scans with 256 A-scans each; CASIA2: 16 B-scans with 800 A-scans each) [8,21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been published several studies analyzing the agreement among instruments based on these techniques to measure WTW. These studies have analyzed the interchangeability of OCT devices and Scheimpflug cameras [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. New devices in the market and the possibility to use them to measure this distance make interesting their analysis to ascertain if there are differences between them.…”
Section: Introductionmentioning
confidence: 99%
“…Savini et al reported that the mean value of the SS-OCT biometer was higher than that of the PCI 13 . Liao et al also showed that the mean LT measured using SS-OCT was higher than that measured using PCI in the Bland–Altman analysis 14 . These results are consistent with our findings, which demonstrate that 4.35 and 4.40 mm in the LT inspection group are IOL master 700 (PCI) and CASIA2 (SS-OCT), respectively.…”
Section: Discussionmentioning
confidence: 94%